Effect of Delayed Cord Clamping on Breastfeeding Behaviors During the First Breastfeed: A Randomized Controlled Study - Hosagasi, Nihan Hilal; Gungor, Sami (Mary Ann Liebert, Inc, 2024)
Objective: Delayed cord clamping (DCC) may increase the success of breastfeeding by improving neurological and cardiovascular function in neonates. In this study, we investigated the impact of DCC on breastfeeding behaviors, neonatal activity status, and maternal satisfaction during the first breastfeeding.Methods: This randomized controlled study was conducted in a tertiary hospital in Turkey with 100 term infants delivered by elective cesarean section with spinal anesthesia. The participants were randomly assigned to the early cord clamping (ECC) group or DCC group. The Infant Breastfeeding Assessment Tool (IBFAT) was used to assess infant alertness, breastfeeding behaviors, and maternal satisfaction with breastfeeding within the first 2 hours of life.Results: Scores on the IBFAT were significantly higher in the DCC group compared with the ECC group (p = 0.02). Maternal satisfaction with breastfeeding did not differ between the groups (p = 0.3). Infant alertness tended to be better in the DCC group, but the difference was not statistically significant (p = 0.08).Conclusion: The results of this study indicated that DCC was associated with more favorable breastfeeding behaviors compared with ECC.
Keywords: breastfeeding; newborn; breastfeeding assessment tool; delayed cord clamping